2017
DOI: 10.3390/su9122307
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Business Case and Models for Sustainable Multifunctional Edible Landscaping Enterprises in the Phoenix Metro Area

Abstract: This study assesses whether multifunctional edible landscaping business models provide a sufficient business case at enterprise and city scales to justify widespread implementation. First, semi-structured interviews were conducted with four landscaping entrepreneurs, and the information obtained from the interviews was utilized to carry out a business model comparison with the Business Model Canvas framework. The comparison showed that the landscaping enterprises using multifunctional edible landscaping method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Furthermore, the most important point is that the benefits of edible landscape development far exceed the benefits of traditional agricultural production. As Robinson et al [43] showed in their study, multifunctional edible landscapes have the potential for high returns on creation and investment. There are even economic benefits for urban municipalities, mainly in terms of reduced municipal expenditure on greenery maintenance and management [44].…”
Section: Discussion: How To Promote Edible Landscapes Through Place B...mentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the most important point is that the benefits of edible landscape development far exceed the benefits of traditional agricultural production. As Robinson et al [43] showed in their study, multifunctional edible landscapes have the potential for high returns on creation and investment. There are even economic benefits for urban municipalities, mainly in terms of reduced municipal expenditure on greenery maintenance and management [44].…”
Section: Discussion: How To Promote Edible Landscapes Through Place B...mentioning
confidence: 90%
“…As an emerging sustainable development concept, studies have found that the development of edible landscapes is very beneficial to local development. For example, Robinson et al [43] found that the development of edible landscapes in the Phoenix area has significant economic benefits and is very conducive to the economic development of the area. Lafontaine-Messier [44] found that the development of edible landscapes in the southern part of Lima, Peru, could increase the economic income of the local municipality, reduce financial support, and also bring economic benefits to local producers and promote local economic development.…”
Section: Place Brandmentioning
confidence: 99%
“…Robinson, Cloutier, and Eakin [60] prove that the landscaping enterprises have a sustainable business model, thereby provide multifunctional edible landscapes in the cities, have a greater range of value propositions and revenue streams resulting in increasing their competitive advantage. They express that these enterprises can have the potential value creation of edible landscaping ranged between $3.9 and $66 billion and that positive return on investment (ROI) could be achieved within one to five years.…”
Section: Agri-foodmentioning
confidence: 99%
“…Benefit research involves a wide range of disciplines and has yielded numerous findings. These include economic benefits, such as crops output (Robinson et al, 2017); health benefits, such as improving physical and psychological conditions (Taylor et al, 2017); ecological benefits, such as biodiversity improvement (Fischer et al, 2019); social benefits, such as promoting social interaction between teachers and students (Laaksoharju et al, 2012); and education benefits, such as imparting agricultural knowledge (Schreinemachers et al, 2017). Research on edible campus design involves integrating agriculture with the campus built environment, such as vertical agriculture (Zhang et al, 2018) and hydroponic roof (Jans-Singh et al, 2020;Ledesma et al, 2020); the design of campus waste recycling systems, such as cafeteria kitchen waste reuse systems and circular food systems (Cahyanti et al, 2019;Erälinna and Szymoniuk, 2021;Torrijos et al, 2021); and multi-subjects collaborative design approach, such as organizing students and medical school patients to collaborate in designing campus garden (Dantas et al, 2018).…”
Section: The Importance Of Edible Campus Design Researchmentioning
confidence: 99%
“…Regarding spatial carrier, large and concentrated planting spaces can produce high yields at low cost (Roggema, 2021), thus promoting economic output. On the other hand, the construction of pedestrian roads is challenging, and the space area allocated for pedestrian roads is relatively small, which makes it difficult to balance income and expenditure and is not conducive to the economic benefit (Robinson et al, 2017). Therefore, pedestrian roads show a negative correlation.…”
Section: Economic Output Benefit and Design Factorsmentioning
confidence: 99%